2005
DOI: 10.1016/j.febslet.2005.02.037
|View full text |Cite
|
Sign up to set email alerts
|

JM4 is a four‐transmembrane protein binding to the CCR5 receptor

Abstract: The CC chemokine receptor 5 (CCR5) is a major coreceptor for human immunodeficiency virus (HIV) and CCR5 mutants lacking the carboxy (C)-terminus interfere with HIV infection. Therefore, we analysed the C-terminus of CCR5 and here describe Jena-Muenchen 4 (JM4), a novel CCR5-interacting protein. JM4 is membrane-associated, co-precipitates with CCR5, and is ubiquitously expressed. It shares about 62% sequence similarity with JWA and glutamate transporter-associated protein 3-18 (GTRAP3-18), a regulator of an am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 37 publications
2
65
0
Order By: Relevance
“…Mouse PRA1 export from the ER to the Golgi was shown to depend on homodimerization (Liang et al, 2004). The PRA1 domain-containing protein Jena-Muenchen 4 (JM4) forms a multimeric complex (Schweneker et al, 2005). We have observed homodimerization and heterodimerization among members of the AtPRA1 family.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Mouse PRA1 export from the ER to the Golgi was shown to depend on homodimerization (Liang et al, 2004). The PRA1 domain-containing protein Jena-Muenchen 4 (JM4) forms a multimeric complex (Schweneker et al, 2005). We have observed homodimerization and heterodimerization among members of the AtPRA1 family.…”
Section: Discussionmentioning
confidence: 74%
“…This is not the first time that a PRA1 protein was found simultaneously in different compartments within the same cell. The human PRA1 domain-containing protein JM4 is present in the trans-Golgi, endosomes, and ER (Schweneker et al, 2005). In yeast, Yip3p was found in COPII vesicles through mass spectrometry (Otte et al, 2001), while rat PRA1 was identified in Golgi and COPI vesicles (Gilchrist et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several JWA homologues (e.g., ARL-6, GTRAP3-18, addicsin and JM4) were since identified (Butchbach et al, 2002;Schweneker et al, 2005). These homologues contain a large prenylated Rab acceptor 1 domain, believed to form a new family of ADP-ribosylation factor proteins that has a role in the regulation of intracellular protein transport (Ingley et al, 1999).…”
Section: Introductionmentioning
confidence: 99%